2008
DOI: 10.1021/la702481v
|View full text |Cite
|
Sign up to set email alerts
|

The Build-Up of Polyelectrolyte Multilayers of Microfibrillated Cellulose and Cationic Polyelectrolytes

Abstract: A new type of nanocellulosic material has been prepared by high-pressure homogenization of carboxymethylated cellulose fibers followed by ultrasonication and centrifugation. This material had a cylindrical cross-section as shown by transmission electron microscopy with a diameter of 5-15 nm and a length of up to 1 microm. Calculations, using the Poisson-Boltzmann equation, showed that the surface potential was between 200 and 250 mV, depending on the pH, the salt concentration, and the size of the fibrils. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
657
3
13

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 777 publications
(693 citation statements)
references
References 45 publications
20
657
3
13
Order By: Relevance
“…Recently the development in cellulosic fibrillation methods has facilitated the production of nano-scaled NFC from cellulosic sources like wood and crops with reasonable low energy consumption. [1][2][3] The width of the nanofibrils depends on the production method but is typically around 5-20 nm. The length of the fibrils 3 is more challenging to determine but may exceed 5 µm and thus the aspect ratio of NFC is more than 250.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the development in cellulosic fibrillation methods has facilitated the production of nano-scaled NFC from cellulosic sources like wood and crops with reasonable low energy consumption. [1][2][3] The width of the nanofibrils depends on the production method but is typically around 5-20 nm. The length of the fibrils 3 is more challenging to determine but may exceed 5 µm and thus the aspect ratio of NFC is more than 250.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to thickness development (figure 4), the buckling wavelengths show a linear propagation as well (figure 5a), with an increasing rate for PVAm-SiO 2 -PVAm-NFC than for PVAm-NFC. It has been reported elsewhere [1][2][3][4][5] that the buckling wavelength increases with increasing the number of layers. The Young' modulus, however, should not be affected by thickness over a certain thickness range [9][10][11][12][13] which is also demonstrated here in figure 5b.…”
Section: Resultsmentioning
confidence: 82%
“…It has for example been shown that the CNC can selforganize [2] to give a chiral nematic arrangement of the CNC film as water is evaporated from the CNC dispersion. It has also been shown that both CNC and NFC can be incorporated into Layer-by-Layer (LbL) self assemblies to yield films with controlled thickness and hence controlled optical properties depending on the composition of the film [3,4]. Recent investigations have also shown that it is possible to prepare freestanding films on NFC [5,6] with controlled barrier properties and with very low oxygen permeabilities at low relative humidities (RH).…”
Section: Introductionmentioning
confidence: 99%
“…NCC is made by hydrolysis, generally using inorganic acids (e.g., sulfuric acid and phosphoric acids), and produces highly crystalline and rigid nanoparticles. [13][14][15][16] Since the amorphous region of the cellulose fibril is degraded in the process, the yield is low (30-50% yield, <7 MJ kg −1 energy consumption of the nano conversion). NFC fabrication from wood-derived pulp fibers was first achieved by mechanical agitation (high energy consumption, generally >30 000 kWht −1 , 700-1400 MJ kg -1 ) [7,13,14] and chemical-mechanical methods, e.g., the carboxymethylation route (high energy, generally >30 000 kWht −1 , 700-1400 MJ kg −1 ).…”
Section: Doi: 101002/gch2201700045mentioning
confidence: 99%